An Evaluation of College Students Perceptions of English Grammar Teaching Strategies - Sadabillah, Hunain; Aniuranti, Asfi; Tsani, M. Happy Nur (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
Nowadays, the centre of teaching learning process is the students. Their opinions or perceptions about teaching and learning process are always considered essential. This research explores the students perceptions of the strategies implemented in English Grammar class. This study employed the quantitative approach. The researchers delivered a closed questionnaire to the students to find out their perceptions. The results revealed a positive perception of the teaching strategies implemented by the lecturers in teaching English grammar. It can be seen from the results of the questionnaires that the students dominantly agreed to the questionnaires. 52.9% of the students agreed to Inductive Approach, 52.9% agreed to Text-Context, 50% of the students agreed to Interactive Activities, 52.9% strongly agreed to Games, and 47.1% agreed to Written Practice.